PERFORMANSI PENGELOLAAN KEBUN HUTAN (FOREST GARDEN) KAYU MANIS DI DESA LOK LAHUNG KECAMATAN LOKSADO KABUPATEN HULU SUNGAI SELATAN - Rizal Anshari; Hafizianor Hafizianor; Badaruddin Badaruddin (EnviroScienteae, 2022)
Cinnamon forest garden are important income resource for farmer on Lok Lahung Village, Loksado Subdistrict. Forest garden’s existence gives great impact on its surrounding’s life. Therefore, strategic approaches should be done to support the management’s performance. Aims of the study are to identify potency and distribution, analyze the management system, analyze stakeholder’s role and influence on cinnamon forest garden’s management, and analyze local community forest garden management’s performance on Lok Lahung Village, Loksado Subdistrict, Hulu Sungai Selatan Regency, South Kalimantan. Based on the results, cinnamon forest garden in Lok Lahung Village have average of  trees on plot and cinnamon potency/ha are 38 trees and 394,726 m³/ha. All farmer (100%) in Lok Lahung Village have cinnamon forest garden which are managed independently with family, start by land preparation, seed preparation, planting, maintenance, harvesting, marketing and post harvest land treatments. Identified stakeholders on cinnamon forest garden’s management are: Hulu Sungai Selatan Local Government, KPH Hulu Sungai, Cinnamon Farmer and Collector/ Merchant are key player, Lok Lahung Village Government, Farmer Group, and Public Figure/Indigenous Public Figure are context setter, and University is crowd. Forest garden management’s performance on Lok Lahung Village are good with total value 334.